1974
DOI: 10.1136/thx.29.6.654
|View full text |Cite
|
Sign up to set email alerts
|

Use of BCG as an immunostimulant in the surgical treatment of carcinoma of the lung

Abstract: -658. Use of BCG as an immunostimulant in the surgical treatment of carcinoma of the lung. Cell-mediated immunity to cancer cells would appear to exert some control over the extension of tumour growth, and stimulation of this factor might result in increased survival after surgical treatment of the tumour. Of the various agents used as stimulators in experimental work, BCG would seem to be the most convenient to use in man. A single dose of BCG-Glaxo (500,000 organisms) was given subdermally 10 days after exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A recent study (McKneally et al, 1977) has shown a statistic, ally significant increase in survival rate at 1 year in Stage I tumours following the single intrapleural injection of BCG -Tice in a dose of 107 viable units. However, Edwards and Whitwell (1974) found no statistically significant increase in survival at a year following the single subdermal injection of BCG -Glaxo in a dose of 0.5 x 106 viable units.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study (McKneally et al, 1977) has shown a statistic, ally significant increase in survival rate at 1 year in Stage I tumours following the single intrapleural injection of BCG -Tice in a dose of 107 viable units. However, Edwards and Whitwell (1974) found no statistically significant increase in survival at a year following the single subdermal injection of BCG -Glaxo in a dose of 0.5 x 106 viable units.…”
Section: Discussionmentioning
confidence: 81%
“…It is not clear, however, whether this effect really depends upon regional application of the vaccine, since beneficial effects have also been observed in lung cancer following administration of BCG at distant intra-dermal sites (Pines, 1976;Edwards and Whitwell, 1974). However, Yamamoto et al (1975) have shown, in the guinea-pig, that a delayed hypersensitivity reaction in the pleural cavity, in response to intrapleurally injected PPD, does produce histological changes in lung tissue as well as in the pleural space.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several trials of various types of immunotherapy in lung cancer [1,5,7,14,17,19,20]. One of the immunotherapeutic agents reported to be useful in disseminated lung cancer is Corynebacterium parvum [14].…”
Section: Introductionmentioning
confidence: 99%